The Effect of Humor on The Innovative Output with Innovative Work Behavior as Variable of Medition - Yulianah, Desy Mulyani (Universitas Negeri Semarang, 2021)
The aim of this research is to know the role of innovative work behavior mediation on the relationship of humor to the innovative output. The population in this study is all owners of SMEs in the Semarang city. Methods of data collection using observation, interview, and questioners. Sampling technique using multiple random sampling. The sample size is 201 SMEs actors. Methods of data analysis using descriptive analysis, validity and reliability test, and hypothesis test. Data analysis using WarpPLS software version 7.0. The results showed that humor increases innovative work behavior and innovative output. In addition, innovative work behavior also increase innovative output. Furthermore, this study found the effect of humor on innovative output can be mediated by innovative work behavior.